The development of a dynamic capabilities framework for leading and managing digital transformation initiatives, integrating change management - Oosthuizen, Chiara (Stellenbosch : Stellenbosch University, 2025)
Oosthuizen, C. 2025. The development of a Dynamic Capabilities framework for leading and managing Digital Transformation initiatives, integrating Change Management. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/9ffbb972-2cc1-4a64-87f3-68c48baa45de